THE MAIN STAGES BETWEEN UKRAINE AND NATO COOPERATION (1991–2021) - ZNAK, Vitalii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The article analyzes the main stages of cooperation between Ukraine and NATO from the simplest forms to the enhanced cooperation of Euro-Atlantic integration, followed the evolution of reaching the level of strategic partnership, taking into account the challenges and demands of the modern world order. The study of Ukraine's cooperation with the North Atlantic Alliance is based on the principles of historicism, objectivity and systematic research. The work methodology also includes a complex of scientific approaches, general scientific methods and special historical methods. The main events from the establishment of close contacts between the top military and political leadership of Ukraine and the Alliance are systematically highlighted, the events where issues of mutual interest to both NATO and Ukraine were discussed. The article offers the author's vision of the main stages of cooperation between Ukraine and NATO, the main trends of the complex transition from cooperation to strategic partnership, the dynamics of priorities and prospects in the conditions of modern challenges and risks facing Ukraine on its way to NATO membership. It has been proven that Ukraine's cooperation with the North Atlantic Treaty Organization is an important component of the new European security architecture. Our country should strengthen its defense capabilities, continue security and defense reforms according to alliance standards. The ultimate goal of our state is victory in the war started by Russia and joining the North Atlantic Alliance, European integration and strengthening of security. The historical discourse of Ukraine–NATO relations in 1991–2021 is an important component of the overall historical process of Euro-Atlantic integration in modern conditions.